Question asking exposure for autistic junior-high school students' English Production - nilam wati (IJET (Indonesian Journal of English Teaching), 2019)
The bibliography suggests students with autism to use verbal contact for communicating, but they are lack in the language production. This study is to observe whether the using of question-asking exposures for students with Autism Spectrum Disorder in the application of WH questions will attract them to answer it and whether they give feedback responses. In the context of qualitative research that being conducted through junior high school students with autism, the data showed that there were improvements in the students’ language production and in the feedback responses. The results lead to the further research that in the context of teaching students with autism, the use of WH questions can be more explored.